Il giorno giovedì 2 marzo 2023 alle 18:00:03 UTC+1 Alberto Rasà ha scritto:
...
> Corrige:
> [Q, Somme_{n=0}^oo a_n P^n] = =Somme_{n=0}^oo a_n [Q, P^n] = ihbar + ihbar Somme_{n=1}^oo a_n n P^{n-1}
> = ihbar Somme_{n=0}^oo a_n dP^n/dP = ihbar (d/dP) [Somme_{n=0}^oo a_n P^n] = ihbar dF/dP.
>
C'era un ihbar di troppo :-)
Corrige-2:
[Q, Somme_{n=0}^oo a_n P^n] =
= Somme_{n=0}^oo a_n [Q, P^n] = ihbar Somme_{n=1}^oo a_n n P^{n-1}
= ihbar Somme_{n=0}^oo a_n dP^n/dP =
= ihbar (d/dP) [Somme_{n=0}^oo a_n P^n] = ihbar dF/dP.
--
Wakinian Tanka
Received on Fri Mar 03 2023 - 15:35:13 CET